Ozone Generator by Using Dielectric Barrier Discharge Plasma Technology With Spiral-Cylinder Configuration: Comparison Between Oxygen and Air As Sources - Nur, Muhammad; Supriati, Aris; Hari Setyaningrum, Dyah; Gunawan, Gunawan; Munir, Mohammad; Sumariyah, Sumariyah (BERKALA FISIKA, 2009)
The ozone generator with Dielectric Barrier Discharge Plasma Technology (DBDPT) with Spiral-cylinder configuration has been developed. DBDP Reactor was constructed with spiral wire and cylinder. Plasma condition has been generated by using AC high voltage Ozone has been produced by this technology with oxygen and dry air as sources for ozone generating. In this research we found that the concentration of ozone produced increases with increasing voltage with a time constant. This concentration also increases with increasing time in certain applied voltage. Ozone concentration was higher than the concentration of dissolved ozone in water. Dissolved ozone in water was only 10 % of ozone produced and only 7 % for dry air as source. Oxygen as source of ozone was better than dry air; both for ozone produced and dissolved ozone in water. Â Keyword : Ozone, Spiral-cylinder, DBDP, Oxygen, Dry air